The Effect of Customer Bonding, Customer Experience, and Service Quality Satisfaction on Customer Loyalty At Novi Tenggarong Salon - Ondi Prawiradinata; Fitroh Adhilla; Zunan Setiawan (ASTEEC, 2026)
Increasingly fierce competition in the beauty services industry has prompted small businesses such as Salon Novi in Tenggarong to prioritize customer loyalty as a key determinant of business sustainability. A quantitative survey approach was used, involving 75 customer respondents selected through probability sampling from a monthly population of 150 customers. Data were collected using a Likert-scale questionnaire and analyzed via multiple linear regression, supplemented by an F-test for simultaneous effects and a t-test for partial effects. The results indicate that customer bonding, customer experience, and service quality simultaneously exert a significant influence on customer loyalty. Partially, all three variables were significant, with service quality emerging as the most dominant (r = 0.486), followed by customer experience (r = 0.472) and customer attachment (r = 0.287), indicating that service quality is the most decisive variable for customer loyalty at Salon Novi Tenggarong.